Poverty and the Millennium Development Goals Pobreza e Metas de Desenvolvimento para o Milênio - G. J. Ebrahim (Instituto Materno Infantil de Pernambuco, 2007)
Poverty has been defined variously at different times in different countries. An early attempt in 1899 in Britain was based on resources necessary for survival. This subsistence standard definition has been used as a measuring rod in one form or another in different countries. For example, less than half the average income has been used as a measure in Britain, and minimum wage or multiples of it in Latin America, and so on. Unless a proper definition of poverty can be agreed attempts at its alleviation can have no target to aim for. Alleviation of poverty, though championed by political leaders of all types has proven to be difficult because equitable division of the national budget requires consensus which is not always forthcoming when the "haves" control the levers of power and the "have nots" must make do with what they get. Measuring collective poverty on a global scale has been attempted by several international agencies. The definition used by the World Bank is stark - "people who live on US $1 per day". According to this definition in the Year 2001 one billion people lived in poverty with consumption levels of US $1 or less per day, and 2.7 billion on less than US $2 per day. Now that more than half the world's population is living in cities, urban poverty is presenting a challenge in most developing countries. Within the physical environment of deprivation there develops a culture of poverty with its prevalence of disease, social disruption, violence in the home and outside, and dependence on drugs and alcohol. In the mind set of the urban poor risk taking behaviour is common. The main victims of deprivation are women and children, the aged and the infirm. Evidence is presented to show the stultifying effects on children growing up in poverty. Remedial action is an uphill task, expensive and not always successful. An awakening of social conscience globally brought about by the stark realities of the urban poor living cheek by jowl in close vicinity of affluence and conspicuous consumption has led enlightened world leaders and economists to mobilise public opinion. A meeting of world leaders held at UN headquarters in the Year 2000 proposed and agreed Millennium Development Goals. The goals address not only poverty per se but also its effects. The target date for achieving the Millennium Development Goals is set at Year 2015.Progress towards the target has been patchy and depends upon national political maturity. A pobreza tem sido definida de diversas formas em diferentes tempos e em diferentes países. Uma tentativa preliminar na Inglaterra, em 1899, tinha como base os recursos necessários para garantir a sobrevivência. Essa definição padrão de subsistência tem sido usada como um instrumento de medida de uma forma ou de outra em diversos países. Por exemplo, na Inglaterra, uma renda menor do que a metade da renda média do país tem sido empregada como medida de pobreza, enquanto que o salário mínimo ou múltiplos dele tem sido usado na América Latina, e assim por diante. A menos que se chegue a um acordo para uma definição apropriada de pobreza, as tentativas para reduzi-la não alcançarão os seus objetivos O alívio da pobreza, embora proclamado pelos líderes políticos de todos os tipos tem provado ser difícil porque a divisão equânime da renda nacional requer um consenso que nem sempre é atingido quando as "elites" controlam as rédeas do poder e a "não elite" tem que se contentar com o que possui. A medição da pobreza coletiva em uma escala global tem sido realizada por várias agências internacionais. A definição utilizada pelo Banco Mundial é clara - "pessoas que vivem com um US$1 por dia". De acordo com esta definição, no ano de 2001, um bilhão de pessoas vivia na pobreza com níveis de consumo de US$1 ou menos por dia e 2,7 bilhões viviam com menos de US$2 por dia. Agora que mais da metade da população mundial está vivendo em cidades, a pobreza urbana é apresentada como um desafio para muitos países em desenvolvimento. Em um ambiente físico de privação se desenvolve a cultura da pobreza com sua prevalência de doença, desagregação social, violência dentro e fora dos lares e dependência de álcool e drogas. No meio urbano pobre a inserção no comportamento de risco é comum. As principais vítimas de privações são as mulheres, as crianças, os idosos e os fracos. Evidências mostram os efeitos deletérios de a criança crescer em meio à pobreza. Ação corretiva consiste em uma tarefa árdua, cara e nem sempre bem sucedida. O despertar da consciência social global provocado pela dura realidade do pobre urbano vivendo lado a lado em íntimo contato com o consumo opulento e evidente tem persuadido líderes mundiais e economistas a mobilizar a opinião pública. Um encontro de lideres mundiais ocorrido nas Nações Unidas, no ano 2000, propôs e acordou Metas de Desenvolvimento para o Milênio. As metas são dirigidas não apenas para a pobreza per se mas também os seus efeitos. A data limite para a conquista das metas de desenvolvimento do milênio foi estabelecida para o ano 2015. Os progressos em torno dessas metas têm sido toscos e dependem da maturidade política nacional.